A machine learning enhanced structural response prediction strategy due to seismic excitation. Issue 1 (25th January 2021) - Thaler, Denny; Bamer, Franz; Markert, Bernd
Abstract: In this contribution, we present a fast prediction approach to estimate response statistics of the crude Monte Carlo simulation using artificial neural networks. Hereby, the neural network is trained within an initial response subset, based on which a forecast can be evaluated in an early state of the Monte Carlo simulation.